Welche Betriebe in Deutschland sind weiterbildungsaktiv? Nutzung des CVTS Datensatzes zur Analyse der betrieblichen Weiterbildung - Bernd Käpplinger (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2007)
– Based on a comparative literature analysis and empirical data of the European enterprise survey CVTS2 from 1999, this paper discusses which German enterprises are active in offering continuous vocational training. Different multivariate analysis (cluster analysis, probit regression) are run, which lead to the conclusion that enterprise-based vocational training is primarily influenced by qualification analysis on enterprise level, the level of formalised human resources management, technological/organisational innovations, the enterprise size and the economic sector. The importance of a formalised human resources management is especially stressed.
Keywords: 330; Weiterbildung; Mikrozensus; CVTS